Analysis of Performance and Level of Service of the Yos Sudarso Road Section in Baubau City Based on the Pedoman Kapasitas Jalan Indonesia (PKJI) 2023 - Jamiludin Nasir; Budi Witjaksana; Jaka Purnama (Jurnal Teknik Indonesia, 2026)
The Yos Sudarso Road section in Wolio District, Baubau City, is a major road with a strategic function, serving as the main connector between important centers such as the commercial area, Kamali Beach, and Murhum Port. The diverse land-use functions along this road generate high daily activity variations, which directly impact its traffic performance. Currently, Jalan Yos Sudarso is experiencing a decline in performance due to increased traffic volume and significant side friction from commercial activities. This research aims to analyze the traffic flow conditions and the Level of Service (LOS) of the road. The analysis method utilizes the Pedoman Kapasitas Jalan Indonesia (PKJI) 2023, based on primary data from surveys on road geometry, traffic volume, and side friction during peak hours. The traffic flow conditions reveal a very high level of side friction caused by on-street parking and vehicle maneuvers into/out of commercial establishments. This activity effectively reduces the road's effective width, consequently degrading its performance. During the peak hour (09:00–10:00), the number of side friction incidents reached 327 incidents per hour, with a concurrent traffic volume of 918.5 pcu/hour (passenger car units per hour). The analysis results show that the road section's actual capacity is 1,116.9 pcu/hour with a Degree of Saturation (DS) value of 0.82. This indicates congested flow conditions and a Level of Service (LOS) category D. This condition suggests that the road can still function, but it no longer provides an optimal level of service.